2015
DOI: 10.1089/jmf.2014.0130
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective and Renoprotective Effects of Lavender (Lavandula stoechasL.) Essential Oils Against Malathion-Induced Oxidative Stress in Young Male Mice

Abstract: We aimed in the present study to investigate the hepato-and nephroprotective effects of Lavandula stoechas essential oils (LSEO) against malathion-induced oxidative stress in young male mice as well as the possible mechanism implicated in such protection. Animals were divided into eight groups of 12 each: Control, malathion (200 mg/kg b.w.); Various doses of LSEO (10, 30, and 50 mg/kg b.w.), malathion + various doses of LSEO. Malathion and LSEO were daily per orally (p.o.) administered by intragastric gavage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…The antioxidant characteristics of the phenolic compounds in L. stoechas are mainly attributed to their ability to eliminate free radicals; for example, they reduce oxidative stress induced in diabetic rats [74] and have hepatoprotective and renoprotective effects against malathioninduced oxidative stress in young male mice [76].…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…The antioxidant characteristics of the phenolic compounds in L. stoechas are mainly attributed to their ability to eliminate free radicals; for example, they reduce oxidative stress induced in diabetic rats [74] and have hepatoprotective and renoprotective effects against malathioninduced oxidative stress in young male mice [76].…”
Section: Antioxidant Effectmentioning
confidence: 99%
“…An increase in intracellular GPx level induced by LOE has been indicated in earlier reported. 29 At the same time, oral administration of LOE significantly decreases the hepatic MDA of the rats of groups 4 and 5 when compared with the MTX group (p<0.05). These results of LOE might be the schedule for the defense against pathological alterations in liver in rats induced by MTX.…”
Section: Discussionmentioning
confidence: 82%
“…These results were similar to several studies who reported that LOE reversal of enhanced serum enzymes on induced liver damage by Malathion and Alloxan. 28,29 Reactive oxygen species (ROS; •OH, O2-, RO, ROO, NO) play main role in enhance of MTXinduced cellular damages in liver tissue. Induced of oxidative stress due of ROS may lead to initiation and progression of some disease such as cardiovascular, diabetes and neurodegenerative disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that essential oil has hepatoprotective effects in various animal models (Bouzenna et al, 2016[ 14 ]; Jiang et al, 2019[ 43 ]; Morales-López et al, 2017[ 58 ]; Özbek et al, 2016[ 62 ]; Selmi et al, 2015[ 73 ]). P. minus contains various medicinal values and yields high levels of essential oil (72.54 %) mainly of aliphatic aldehydes, terpenoids and organic acids (Baharum et al, 2010[ 10 ]).…”
Section: Introductionmentioning
confidence: 99%